(untitled) (Actualizaciones en Sida e Infectología, 2023)
Kaposi’s sarcoma (KS) is a low-grade angioproliferative malignancy caused by infection with human herpes virus -8. The gastrointestinal tract is involved in 40% of cases, being the most common gastrointestinal malignancy in patients with AIDS. We present the case of a 32-year-old patient with a long-standing history of HIV without treatment, who reported episodes of intermittent proctorrhagia and weight loss in the last two months. He presented raised skin lesions in the form of violaceous plaques that predominate on the trunk and upper limbs. A videocolonoscopy was performed, revealing raised, erythematous, friable, bleeding lesions near the ileocecal valve and in the ascending colon, which were biopsied. The anatomopathological study shows an immunohistochemical profile compatible with KS. At the time of writing this article, the patient was under chemotherapy treatment (liposomal doxorubicin, 6 cycles) and starting antiretroviral treatment (lamivudine - tenofovir - dolutegravir). The following case is presented to highlight the importance of the multidisciplinary approach of the patient with HIV / AIDS and fundamentally the role of both upper and lower digestive endoscopy in those cases that present with abdominal pain, digestive bleeding and other abdominal symptoms, in order to rule out gastrointestinal tract pathologies and particularly KS.